2017
DOI: 10.3325/cmj.2017.58.34
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in completed suicide: a forensic-pathological pilot study

Abstract: AimTo determine whether antemortem blood levels of glycated hemoglobin (HbA1c) and glucose predict completed suicide and, by extension, whether markers of glucose metabolism might be associated with a prosuicidal trait or state.MethodFrom consecutively performed autopsies, samples of blood and vitreous humor from 17 suicide victims and 27 non-suicide controls were compared with regard to levels of glucose, lactate, and HbA1c.ResultsMean HbA1c was higher and mean estimated blood glucose was lower among suicide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Research also suggests that blood glucose levels are associated with suicide risk. A pilot study suggested that abnormal glucose metabolism may reflect biological changes prior to or concomitant with suicide [19]. Diabetes mellitus among patients with depression is also associated with a higher rate of suicide attempts [20].…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests that blood glucose levels are associated with suicide risk. A pilot study suggested that abnormal glucose metabolism may reflect biological changes prior to or concomitant with suicide [19]. Diabetes mellitus among patients with depression is also associated with a higher rate of suicide attempts [20].…”
Section: Introductionmentioning
confidence: 99%
“…To begin with the regulation of glucose import in response to insulin stimulus GO has not been per se linked with SB; nevertheless, it is not the case of the glucose metabolism and insulin related. For example, Forsman et al () studied 17 SV and 27 nonsuicide controls and compared glucose lactate levels and HbA1c; they found that mean HbA1c was higher and mean estimated blood glucose was lower among SV. In addition, there is a hypothesis that hyperglycemia and hyperinsulinemia may increase the risk for depression and suicide; the group of Koponen, Kautiainen, Leppanen, Mantyselka, and Vanhala () studied the associations between SB and disturbances in glucose metabolism in depressive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The total inventory score is obtained by summing the 21 items, yielding a total score ranging from 0 to 63. Thus, the score range indicates a: minimal depression (0-13), a mild depression (14)(15)(16)(17)(18)(19), a moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and a severe depression .…”
Section: Bdi-iimentioning
confidence: 99%
“…A current hypothesis suggests that physical exercise, like recreational running, stimulates blood lactate production, with this biomarker having antidepressant effects due to psychological processes regulation. This regulation mechanism results from increased intracellular glucose availability to the brain 20 . In this view, low lactate blood levels could be an interesting indicator of depressive symptom development 21,14 , leading to alternative pathways to treat depression, such as physical activity, associated with lactate stimulation.…”
Section: Introductionmentioning
confidence: 99%